2011
DOI: 10.1080/00335630.2010.536565
|View full text |Cite
|
Sign up to set email alerts
|

Still Burning: Self-Immolation as Photographic Protest

Abstract: This poetic inquiry paper is a reflection on the phenomenon of self-immolation committed as compassionate protest. Whether the self-directed social protest of Vietnamese monk, Thích Quảng Đức, and Tibetan monastics and lay people, expresses selfless, altruistic action, dedicated to the greater good, merits investigation. Individuals seeking social justice in today's troubled times may be interested in cultivating ahimsa, or non-violence, within themselves before attempting to actualize it within their communit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…As such, it is a way of metaphorically construing and narrating experience; a compelling narrative enjoining others to take action ( 41 ). This is an utterance, a communicative act with the consequent potential to promote agency and civic engagement ( 42 ) which demands a response from the addressee, the Other. It demands and forces social recognition.…”
Section: Discussionmentioning
confidence: 99%
“…As such, it is a way of metaphorically construing and narrating experience; a compelling narrative enjoining others to take action ( 41 ). This is an utterance, a communicative act with the consequent potential to promote agency and civic engagement ( 42 ) which demands a response from the addressee, the Other. It demands and forces social recognition.…”
Section: Discussionmentioning
confidence: 99%
“…The topic of self-immolation has seen its fair share of scholarly attention, especially among sociologists (Robbins 1986;Park 2004;Biggs 2005) and anthropologists (Andriolo 2006;Makley 2015). It has been addressed in discussions as diverse as photographic protest (Yang 2011) and the role of women in peace movements (Cheyney 1994). However, the visual aspects of self-immolation as a distinctly material kind of contentious performance-in particular, its spectacularity, visuality, 4 and physicality-remain largely unaddressed.…”
Section: Theorizing the Body-on-firementioning
confidence: 99%
“…Several scholars have suggested that self-immolation ought to be "read" as a form of suicide in terms of its agency and performance. Yang (2011), in her close visual analysis of Malcolm Browne's photograph of the Buddhist monk Thích Quảng Đức (see figure 9.1), examined how appropriations of the burning monk's image demonstrate the resonance of "about to die" moments and their potential to promote agency and civic engagement. At the same time, Jaworski (2010) offers a feminist critique of this perspective, suggesting that the suicidal act is relational, and as such never outside of discourse and power relations.…”
Section: Theorizing the Body-on-firementioning
confidence: 99%
See 1 more Smart Citation